Temporal cycles and spatial asynchrony in the reproduction and growth of a rare nectarless orchid, Cypripedium calceolus - Sonja Hurskainen; Anne Jäkäläniemi; Veijo Kaitala; Tiiu Kull; Marilin Mõtlep; Satu Ramula; Juha Tuomi (WILEY, 2022)
The timing and intensity of plant reproduction vary due to internal and external factors. Although this variation has been widely studied in species exhibiting masting (intermittent synchronous reproduction), it has attracted less attention in nonmasting species. Here, we studied intra-individual variation in the flowering intensity and plant size of a nonmasting, rare terrestrial orchid, Cypripedium calceolus, using long-term monitoring data from three populations in Finland and two populations in Estonia. Flowering intensity and plant size showed 2-year cycles, indicating that reproduction and growth were regulated by past costs of reproduction and extensive clonal growth. In addition, flowering intensity and plant size were positively correlated with size from the previous year and were also affected by the weather conditions of spring and of the previous growing season. However, there was little synchrony among plants, suggesting that the climatic control of reproduction and growth is sufficiently low as to be masked by high annual variation in these two vital rates. Together, these results indicate that the reproduction and growth of C. calceolus depend on individual demographic history and past weather conditions and that intrinsic factors can also lead to cyclic fluctuation in reproduction in nonmasting species.